An inquiry into post-competition performance of business plan competition teams. - Wu, Jia Min. (2013)
A common aim of a business plan competition (BPC) is to develop essential entrepreneurial skills in the participants and eventually aid them in creating sustainable businesses. The ability to nurture sustainable businesses has since been a key outcome of many BPCs. Despite that, little research has studied the relationship between the participating teams’ performance at BPC and their business survival after the competition. Our study seeks to study this relationship, specifically, whether teams that performed well at BPC could perform well thereafter, and the reasons for such performance after BPC. Correlation analyses performed on 193 teams from the United States (US) and Singapore BPCs showed that performance at BPC was positively correlated to performance after the competition. Interviews conducted with four teams from the Singapore BPC revealed the four broad categories of factors that enabled businesses to survive after the competition, namely the human, intellectual, social, and financial capital. As the factors derived from the BPC were not the differentiating factors between the teams that survived and teams that did not survive, this showed that BPC had partial effect on the performance of teams after BPC.